2024
DOI: 10.3390/f15010208
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution Analysis of Spatial Vitality of Specialized Garden Plant Landscapes during Spring: A Case Study of Hangzhou Botanical Garden in China

Tian Liu,
Bingyi Mi,
Hai Yan
et al.

Abstract: Specialized gardens, as integral components of botanical gardens, bear multiple functions, encompassing plant collection and conservation, scientific research, and public education, as well as serving aesthetic and recreational purposes. Their quality profoundly reflects the landscape artistry of botanical gardens, directly influencing the quality of visitors’ enjoyment and the overall experience within the botanical garden. This study aims to investigate the spatial vitality of specialized garden plant landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They suggested that the significant relationship between objective or subjective landscape complexity, or preference and eye movement metrics, was dependent on landscape types. Liu et al examined the spatiotemporal distribution patterns of spatial vitality and explored the correlation between plant landscape characteristics and spatial vitality [20]. They suggested that to establish vibrant specialized plant landscapes, managers and planners involved in the planning and design process should prioritize a comprehensive consideration of and respect for the visual aesthetics and functional needs of visitors.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%
“…They suggested that the significant relationship between objective or subjective landscape complexity, or preference and eye movement metrics, was dependent on landscape types. Liu et al examined the spatiotemporal distribution patterns of spatial vitality and explored the correlation between plant landscape characteristics and spatial vitality [20]. They suggested that to establish vibrant specialized plant landscapes, managers and planners involved in the planning and design process should prioritize a comprehensive consideration of and respect for the visual aesthetics and functional needs of visitors.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%